Inside the dark web - Ozkaya, Erdal (CRC Press, 2019)
Introduction to cybersecurity and dark web -- Threat landscape in Dark net -- Malicious darknet, or network -- Malware -- Cybercriminal activities in Dark net -- Evolution of the web and its hidden data -- Dark web content analysing techniques -- Extracting information from dark web contents/logs -- Dark web forensics -- Open source intelligence -- Emerging trends in the dark web and mitigating techniques.